2002
DOI: 10.1017/s0265021502000716
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of successful neuraxial block: a prospective study

Abstract: The successful location of the subarachnoid or the epidural space at the first attempt is influenced by the quality of patients' anatomical landmarks, the adequacy of patient positioning and the provider's level of experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(69 citation statements)
references
References 12 publications
2
63
4
Order By: Relevance
“…With a first-attempt rate of 441/500 (88.2%), the practicability of the spinal anaesthesia was comparable or higher than that in studies of other authors comparing the success rates of experienced anaesthesiologists (Sprung: 87%, de Oliveira Filho: 71.4% [17,18] ). Side effects such as hypotension and bradycardia were lower than in the related literature [5,19] , probably due to the low dosage of heavy bupivacaine.…”
Section: Saddle Block Anaesthesia and Recoverymentioning
confidence: 56%
“…With a first-attempt rate of 441/500 (88.2%), the practicability of the spinal anaesthesia was comparable or higher than that in studies of other authors comparing the success rates of experienced anaesthesiologists (Sprung: 87%, de Oliveira Filho: 71.4% [17,18] ). Side effects such as hypotension and bradycardia were lower than in the related literature [5,19] , probably due to the low dosage of heavy bupivacaine.…”
Section: Saddle Block Anaesthesia and Recoverymentioning
confidence: 56%
“…The extent of the complications vary, ranging from self-resolving events, such as postdural puncture headache [1], to severe incidents, such as permanent neurologic sequelae [2]. Some efforts have been made in order to predict the difficult neuraxial blockade for the purpose of minimizing the risk caused by traumatic placement of the needle [3,4]. However, no absolute predicting factors have been found so far in spite of the efforts.…”
Section: Introductionmentioning
confidence: 99%
“…This might be caused by inadequate difference in lumbar vertebrae furtherance in both groups (15, 16). Many studies have found landmark identification to be one of the important factors for successful spinal anesthesia administration, although its accuracy in evaluating the required intervertebral gaps is poor (1, 4, 9, 25, 26). …”
Section: Discussionmentioning
confidence: 99%
“…Poor positioning may cause repeated spinal needle insertions and spinal needle-vertebrae bone contact, thus increasing the risk of back pain, post-dural puncture headache (PDPH), epidural hematoma, and neural trauma (9). …”
Section: Introductionmentioning
confidence: 99%